2005
DOI: 10.1097/01.scs.0000179662.38172.dd
|View full text |Cite
|
Sign up to set email alerts
|

Allograft and Alloplastic Bone Substitutes: A Review of Science and Technology For the Craniomaxillofacial Surgeon

Abstract: Bone healing is a complex and multifactorial process. As such, there are numerous steps in the process to which intervention can be directed. This has given rise to many bone graft technologies that have been used to regenerate bone, creating, perhaps, a bewildering array of options. The options that surgeons have the most familiarity with are the ones that have been available the longest (i.e., autograft and allograft). Although useful for the widest spectrum of clinical applications, limitations of these gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
0
22

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(135 citation statements)
references
References 87 publications
3
110
0
22
Order By: Relevance
“…From a patient's perspective, the ultimate goal is replacement of their damaged/lost bone with autogenous material, harvested with minimal donor side morbidity. Traditionally, small defects are covered using autologous bone taken from iliac crest or ribs but large bony defects require autografts or allografts whose application is limited in terms of material availability and successful tissue in-growth (Eppley et al 2005). Furthermore, allografts carry the risk of disease transmission and host immune response (Horner et al 2010; Saha et al 2011;Yang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…From a patient's perspective, the ultimate goal is replacement of their damaged/lost bone with autogenous material, harvested with minimal donor side morbidity. Traditionally, small defects are covered using autologous bone taken from iliac crest or ribs but large bony defects require autografts or allografts whose application is limited in terms of material availability and successful tissue in-growth (Eppley et al 2005). Furthermore, allografts carry the risk of disease transmission and host immune response (Horner et al 2010; Saha et al 2011;Yang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard evaluation method used to characterize the fate of the grafted bone over time has been a histological evaluation of a sample of the graft, but in the literature also other methods have been developed for this purpose, mainly biomechanical, biomolecular, and noninvasive imaging methods [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Bone grafts may contain bone morphogenic proteins (BMPs), which are purported to have both bone conductive and inductive effects. 19 Autogenous bone grafts are the gold standard for alveolar ridge augmentation, and are classified as follows: (1) endochondral bone, such as iliac crest and long bones, and (2) intramembranous bone, such as mandibular ramus and symphysis. Kusiak et al, 20 found that intramembraneous (also referred to as membraneous) bone grafts show earlier revascularization compared to endochondral bone blocks.…”
Section: Discussionmentioning
confidence: 99%